New technologies in treatment of iron-deficient anemia - O. N. Minushkin; G. A. Elizavetina; O. I. Ivanova; Y. S. Barkalov (Медицинский совет, 2016)
The article presents the comparative results of treatment of iron-deficient anemia by a specialized therapeutic and preventive product based on a combination of liposomal iron and vitamin C at a daily dosage of 30 (1 capsule) and 60 mg (2 capsules) and a combination drug of bivalent iron and vitamin C at a daily dose of 100 (1 capsule) and 200 mg (2 capsules) for 2 months. The approximately similar results were obtained but they were achieved by lower dosages of drug contained combination of liposomal iron and vitamin C in the absence of side effects.